A Developmental Systems Approach to Exploring the Plasticity and Diversity of Teen Childbearers' Parenting Behaviors - (:unkn) unknown (My University, 2013)
Introduction: Many empirical studies indicate that teen childbearers, in comparison to adult childbearers, are more likely to exhibit maladaptive parenting behaviors, including low responsivity, harsh discipline, and child maltreatment. Yet, it is unclear whether teen childbearers are likely to engage consistently in poor parenting over time, why they may continue to engage in poor parenting, and which teen childbearers are most likely to engage in poor parenting persistently. Methods: This study used secondary data to investigate the person-in-context, temporality, plasticity, and diversity of teen childbearers' parenting behaviors using cross-sectional regressions, latent growth curve models, and joint longitudinal cluster analysis. Results: Analyses conducted in Paper 1 found a temporary, but not a lasting, relation between teen childbearing and aggressive discipline. Paper 2 used latent growth curve models to compare the developmental changes of teen and adult childbearers' aggressive discipline and found that their rate of change did not differ, but rather that teen childbearers were more likely than adult childbearers to use aggressive discipline at young child ages. The study also found that the effect of domestic violence, but not social support or mental health, on aggressive discipline varied between teen and adult childbearers. Paper 3 identified three subgroups of teen childbearers that followed different joint-patterns of adaptive and maladaptive parenting over time, and that high child emotionality, low household income, and high parenting stress were related to the least adaptive parenting pattern. Conclusions: Teen childbearers' parenting changes as their children age, and there is relative plasticity in teen childbearers' parenting. In addition, the results indicate that teen childbearers' parenting behaviors are diverse - diverse in comparison to adult childbearers' and within the population of teen childbearers. Finally, the papers demonstrate the need to consider the teen childbearer in context. Taken together, the results suggest that intervention programs, preferably those that occur prior to the child's birth and that extend through toddlerhood, might prevent the emergence of poor parenting behaviors. Nevertheless, screening and assessment of teen childbearers should be comprehensive in order to best discern which teens are most in need of intervention and in what domains.
Keywords: Adolescent Mothers; Aggressive Discipline; Developmental Systems Theory; Longitudinal; Parenting; Risk Factors